2008
DOI: 10.1021/ie800335j
|View full text |Cite
|
Sign up to set email alerts
|

Production of Very Pure Hydrogen with Simultaneous Capture of Carbon Dioxide using the Redox Reactions of Iron Oxides in Packed Beds

Abstract: A chemical looping process, which uses a packed bed of the various oxides of iron, has been formulated to produce separate, pure streams of H 2 and CO 2 from syngas. The process has the following stages: (1) Reduction of Fe 2 O 3 to Fe 0.947 O in the syngas from gasifying coal or biomass. This stage generates pure CO 2 , once the water has been condensed. (2) Subsequent oxidation of Fe 0.947 O to Fe 3 O 4 using steam, to simultaneously produce H 2 . (3) Further oxidation of Fe 3 O 4 to Fe 2 O 3 using air to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
136
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(146 citation statements)
references
References 20 publications
8
136
0
Order By: Relevance
“…In CLH process, the reaction scheme of iron oxide reacting with the fuel in FR is more complicated than the oxidation reactions occurred in SR and AR [26,27]. The reduction of Fe 2 O 3 generally occurs with the formation of different iron oxides at lower valent state or metallic Fe depending on the employed operating conditions and the properties of oxygen carrier.…”
Section: Reduction Step In Frmentioning
confidence: 99%
“…In CLH process, the reaction scheme of iron oxide reacting with the fuel in FR is more complicated than the oxidation reactions occurred in SR and AR [26,27]. The reduction of Fe 2 O 3 generally occurs with the formation of different iron oxides at lower valent state or metallic Fe depending on the employed operating conditions and the properties of oxygen carrier.…”
Section: Reduction Step In Frmentioning
confidence: 99%
“…Bohn et al [32] proposed Fe 2 O 3 /FeO as the proper redox couple for stable H 2 production in a packed bed reactor because reduction reactivity was lost when Fe 2 O 3 was reduced to Fe. Then, Kierzkowska et al [33] suggested that the addition of 40 wt.…”
Section: Introductionmentioning
confidence: 99%
“…Bohn et al [39] simulated CLHG in a packed bed and obtained hydrogen suitable for use in fuel cells (<25 ppm vol CO). It was suggested that the further reduction of FeO to Fe in the reduction phase was not recommended, because the reactivity of the iron oxide went bad after ten cycles.…”
Section: Introductionmentioning
confidence: 99%